The concept of most responsible in international criminal law and its problematic reception in the Special Jurisdiction for Peace in Colombia - José Manuel Díaz-Soto; Diego Borbón (Frontiers in Political Science)
This perspective article critically explores the concept of “most responsible” within international criminal jurisprudence and its reception by the Special Jurisdiction for Peace (JEP) in Colombia. In the context of Colombia's transitional justice process, the definitions of “most responsible” and “determining participants” play a pivotal role in deciding who should face prosecution and sanctions of effective restriction of liberty for war crimes and crimes against humanity. The article argues that the current conceptual ambiguity within the JEP's legal framework risks conflating accomplices with principal offenders, which could undermine the selective justice model designed to focus on high-level perpetrators. Through a comparative analysis of international criminal tribunals, including the ICTY, ICTR, ICC, and SCSL, the article highlights the importance of clear definitions to avoid excessive judicialization and to align the process with the goals of peace, reconciliation, and restorative justice. This perspective concludes that the lack of precise legal definitions in the JEP could hinder its ability to fulfill its mandate effectively.